Bimetallic Catalysts for Sustainable Chemistry: Surface Redox Reactions For Tuning The Catalytic Surface Composition. Issue 3 (9th January 2023) - Especel, Catherine; Lafaye, Gwendoline; Epron, Florence
Abstract: The development of a bimetallic catalyst for a given reaction requires not only the selection of the appropriate metals M1 and M2 but also the control as far as possible of the distribution of the two metals together and at the support surface in the case of supported catalysts. Preparation methods using redox reactions specifically enable the deposition of a second metal M2 at the surface of monometallic M1 nanoparticles, leading in most cases to core‐shell nanoparticles with strong metal‐metal interactions. Various methods are possible depending on the electrochemical potentials of the species involved: either a direct redox reaction, also named galvanic replacement, or the reduction of an intermediate reducing agent activated at the surface of M1 . In this minireview, the fundamental bases of the preparation of bimetallic catalysts by both types of redox reactions and the recent advances in that domain are described. Abstract : This minireview describes the fundamental bases of the preparation of supported or unsupported bimetallic catalysts by redox reactions and the recent advances in that domain. These preparation methods enable the deposition of a second metal at the surface of monometallic nanoparticles, leading to bimetallic nanoparticles with strong metal‐metal interactions and enhanced catalytic properties compared to their monometallic counterparts.